Association between Gallbladder Ultrasound Findings and Bacterial Culture of Bile in 70 Cats and 202 Dogs. (29th July 2017) - Policelli Smith, R.; Gookin, J.L.; Smolski, W.; Di Cicco, M.F.; Correa, M.; Seiler, G.S.
Abstract : Background: Bacterial cholecystitis often is diagnosed by combination of gallbladder ultrasound (US) findings and positive results of bile culture. The value of gallbladder US in determining the likelihood of bile bacterial infection in cats and dogs with suspected biliary disease is unknown. Hypothesis/Objectives: To determine the value of gallbladder US in predicting bile bacterial culture results, identify most common bacterial isolates from bile, and describe complications after cholecystocentesis in cats and dogs with suspected hepatobiliary disease. Animals: Cats (70) and dogs (202) that underwent an abdominal US and submission of bile for culture were included in the study. Methods: A cross‐sectional study design was used to determine the association of gallbladder US abnormalities and the results of bile cultures, and complications of cholecystocentesis. Results: Abnormal gallbladder US had high sensitivity (96%) but low specificity (49%) in cats with positive and negative results of bile bacterial culture, respectively. Cats with normal gallbladder US findings were unlikely to have positive bile bacterial culture (negative predictive value of 96%). Gallbladder US had lower sensitivity (81%), specificity (31%), positive predictive value (20%), and negative predictive value (88%) in dogs. The most common bacterial isolates were of enteric origin, the prevalence being higher in cats. Incidence of complications after cholecystocentesis was 3.4%. Conclusions and clinical importance: Gallbladder US has a high negative predictive value for bile culture results in cats. This modality is less predictive of infection in dogs. Percutaneous US‐guided cholecystocentesis has a low complication rate.